Вплив водню на електричні параметри n-InSe - Камінський, В.М.; Ковалюк, З.Д.; Товарницький, М.В.; Іванов, В.І.; Заполовський, М.В. (Львівський національний університет імені Івана Франка,, 2020)
The results of studies of the electrical properties of InSe layered crystals hydrogenated from the gas phase are presented. Theoretical models for the description of the temperature dependences of the mobility and electron concentration of hydrogenated, undoped and annealed InSe crystals are proposed. In order to separately determine the effects of hydrogenation and conventional annealing, the studies of a vacuum heat treated sample under similar conditions were carried out. The electrical characteristics of single crystals were investigated in the temperature range $80\div400$ K. It is established that the electrical conductivity and free-electron concentration of hydrogenated InSe crystals significantly increased, and the electron mobility decreased. The increase in the conductivity and concentration is due to the ionization of the hydrogen atoms. The decrease in the mobility for hydrogenated and annealed InSe is due to the scattering of electrons by the localized hydrogen atoms as well as due to structural changes at annealing. It is shown that the dominant mechanisms of charge-carrier scattering that determine the temperature dependence of mobility are the scattering on homopolar optical phonons and the scattering on ionized impurities. In perfect undoped InSe single crystals, only the scattering on optical phonons occurs in the studied temperature range. The temperature dependence of the electron concentration is analyzed in the framework of the model of impurity conduction. We considered three types of impurity states in the band gap: the deep donor, shallow donor and acceptor. The energy and concentration of the levels were determined. The good coincidence of experimental and theoretical results confirms the validity of the chosen model for our materials.
Keywords: indium selenide, hydrogenation, electrical conductivity, mobility, electron concentration